RELEVANSI KONSEP NEGARA HUKUM PANCASILA DENGAN WELFARE STATE DALAM IMPLEMENTASINYA DENGAN PELAYANAN PUBLIK DI INDONESIA - I Ketut Cahyadi Putra (University of Udayana, 2017)
The State of Pancasila Law essentially stems from the principle of kinship, deliberation of consensus based on customary law, and protection of human rights with the principle of balance between the rights and obligations and the function of the law of auxiliary. As contained in the Fifth Precept of Pancasila that is social justice for all Indonesian people, and the opening of the 1945 Constitution of the Republic of Indonesia related to the phrase